Team implicit coordination and emergency team performance - Mumtaz Muhammad Khan; Suleman Aziz Lodhi; Muhammad Abdul Majid Makki (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2010)
Coordination in trauma teams to cope with the challenges of new emerging situations on site and in emergency wards require aligning teams' actions to plans, schedules, targets, etc. Performance of trauma teams in such critical situations needs improvement to save lives. Implicit coordination behavior is an answer to improve the existing situation and can serve as a landmark in achieving high performance by trauma teams. The study was conducted on teams of emergency wards of public hospitals and Rescue 1122 operating in Lahore. It explores the relationship between implicit coordination behavior among team members and team performance by using statistical technique; factor analysis. The data on team implicit coordination processes framework is collected after developing a structured questionnaire. The study shows that there exists positive relationship between team performance and implicit coordination behavior of team members. The study provides guidance to trauma team managers, directors of emergency health service wards and human resource experts to enhance the team implicit coordination behaviors and resultantly, the team performance by saving human lives.
Keywords: 330; Trauma teams; team performance; implicit coordination; Rescue 1122